Improving Children's Interpersonal Intelligence by Adding Quality Time Intensity - Shodiq, Sadam Fajar (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractThe primary objective of this paper is to investigate the correlation between the intensity of quality time and the level of interpersonal intelligence among students at SMA Muhammadiyah 5 Yogyakarta. The study employed a quantitative research methodology, with a sample size of 68 students selected from a larger population of 215 students. This study assessed the degree of family quality time and the level of interpersonal intelligence among students through the administration of a questionnaire to the participants. The findings indicated that the level of family quality time intensity among the participants was moderate, with a percentage of 63.2%. In the interim, it is seen that pupils exhibit a notable level of interpersonal intelligence, amounting to 79.4%. The results of this study suggest that while the degree of family quality time remains moderate, students at SMA Muhammadiyah 5 Yogyakarta exhibit a significant level of interpersonal intelligence. However, it is imperative to address the issue of intensifying family quality time in order to promote social contact and bolster emotional bonds among family members. This, in turn, has the potential to further augment the development of kids' interpersonal intelligence.AbstrakArtikel ini bertujuan untuk menyelidiki hubungan antara intensitas waktu berkualitas dan tingkat kecerdasan interpersonal di antara siswa di SMA Muhammadiyah 5 Yogyakarta. Penelitian ini menggunakan metodologi penelitian kuantitatif, dengan ukuran sampel sebanyak 68 siswa yang dipilih dari populasi yang lebih besar sebanyak 215 siswa. Penelitian ini menilai tingkat waktu berkualitas keluarga dan tingkat kecerdasan interpersonal siswa melalui pemberian kuesioner kepada partisipan. Temuan menunjukkan bahwa tingkat intensitas waktu berkualitas keluarga di antara partisipan adalah sedang, dengan persentase sebesar 63,2%. Sementara itu, terlihat bahwa para siswa menunjukkan tingkat kecerdasan interpersonal yang mencolok, mencapai 79,4%. Hasil penelitian ini menyarankan bahwa sementara tingkat waktu berkualitas keluarga tetap sedang, siswa di SMA Muhammadiyah 5 Yogyakarta menunjukkan tingkat kecerdasan interpersonal yang signifikan. Namun, sangat penting untuk mengatasi masalah intensitas waktu berkualitas keluarga guna meningkatkan kontak sosial dan memperkuat ikatan emosional antara anggota keluarga. Hal ini, pada gilirannya, berpotensi untuk lebih meningkatkan perkembangan kecerdasan interpersonal anak-anak.How to Cite: Shodiq, S.F. (2023). Improving Children's Interpersonal Intelligence by Adding Quality Time Intensity. TARBIYA: Journal of Education in Muslim Society, 10(1), 1-12. doi:10.15408/tjems.v10i1.29000.